2018
DOI: 10.3389/fnbot.2018.00062
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Mina v2 for Robot-Assisted Balance and Locomotion

Abstract: The assessment of the risk of falling during robot-assisted locomotion is critical for gait control and operator safety, but has not yet been addressed through a systematic and quantitative approach. In this study, the balance stability of Mina v2, a recently developed powered lower-limb robotic exoskeleton, is evaluated using an algorithmic framework based on center of mass (COM)- and joint-space dynamics. The equivalent mechanical model of the combined human-exoskeleton system in the sagittal plane is establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Bearing this in mind, it is of particular importance to investigate the human-exoskeleton interaction in terms of potential inferences with human motor control mechanisms. Especially the assessment of human balance is critical to evaluate the compatibility and operator safety of LLExos (Mummolo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bearing this in mind, it is of particular importance to investigate the human-exoskeleton interaction in terms of potential inferences with human motor control mechanisms. Especially the assessment of human balance is critical to evaluate the compatibility and operator safety of LLExos (Mummolo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observation seems consistent with the present study, because compensation by the reflex did not affect motor modules, whereas that by the CPG did. Robot assisted locomotor training is a useful means for treatment of impaired locomotion (Jezernik et al, 2003; Kawamoto et al, 2013; Molteni et al, 2017; Watanabe et al, 2017) and the devices have been drastically improved to date (Beckerle et al, 2017; Gandolla et al, 2018; Mummolo et al, 2018). Tan et al (2018) reported that robotic-assisted locomotor training for stroke patients improves walking speed, step cadence, stance duration percentage of gait cycle, but does not increase the number of motor modules.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the numerical optimization algorithm and its solution via sequential quadratic programming can be found in previous work ( Mummolo et al, 2018b ). The construction method of the balance threshold has been demonstrated for the study of gait and posture stability of human, robot, and exoskeleton systems ( Mummolo et al, 2017 ; Mummolo et al, 2018a ; Mummolo et al, 2018b ; Mummolo and Vicentini, 2020 ; Mummolo et al, 2021 ).…”
Section: Simultaneous Balance Assessment and Training Methodsmentioning
confidence: 99%